Dijital Olgunluk Ile Dinamik Yeteneklerin Etkileşimi: Prisma Temelli Sistematik Analiz (Üçüncü Sektör Sosyal Ekonomi Dergisi, 2025)
This research aims to systematically analyze the studies conducted to determine the factors affecting the relationship between digital maturity and dynamic. In this context, the studies that addressed the concepts of digital maturity and dynamic capabilities together in the Scopus, Web of Science and Google Academic databases are scanned. As a result of the scan, 9 studies were included in the research because they met the determined analysis criteria. Secondary data was used in the research. The PRISMA method was used in the preparation of systematic compilations. In addition, it was determined that 526 studies were conducted between 2012 and 2025 on the concept of digital maturity in the Scopus database and 7,271 studies were conducted between 1994 and 2025 on the concept of dynamic capabilities. These data were examined using the bibliometric analysis method and the research areas related to the concepts were determined. According to the findings, it has been seen that the interaction between digital maturity and dynamic capabilities should be addressed beyond the technology dimension, but also in the context of culture, organizational structure, business processes, customer relations and transformation capability.
Keywords: Dijital Olgunluk; Dijitalleşme; İşletme yetenekleri; Bibliyometrik Yöntem